2017
DOI: 10.1016/j.biortech.2017.08.217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graphene oxide on the performance, microbial community dynamics and antibiotic resistance genes reduction during anaerobic digestion of swine manure

Abstract: A B S T R A C TThe role of graphene oxide (GO) on anaerobic digestion (AD) of swine manure concerning the performance, microbial community and antibiotic resistance genes (ARGs) reduction was investigated. Results showed that methane production was reduced by 13.1%, 10.6%, 2.7% and 17.1% at GO concentration of 5 mg/L, 50 mg/L, 100 mg/L and 500 mg/L, respectively, but propionate degradation was enhanced along with GO addition. Both bacterial and archaeal community changed little after GO addition. AD could well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 48 publications
(45 reference statements)
2
23
0
Order By: Relevance
“…As shown in Figure 5a, the archaeal community was dominated by Methanosphaera, Methanoculleus, Methanosarcina and Methanosaeta throughout the AD process. The relative abundance of Methanosphaera originating from raw manure [34] decreased from 80.3% to less than 62.5% after seven days of fermentation, and further decreased to less than 1% after AD. However, Methanoculleus persistently increased from less than 1% to 22.2-97.2% after AD, with increasing TS.…”
Section: Archaeal Communitymentioning
confidence: 93%
“…As shown in Figure 5a, the archaeal community was dominated by Methanosphaera, Methanoculleus, Methanosarcina and Methanosaeta throughout the AD process. The relative abundance of Methanosphaera originating from raw manure [34] decreased from 80.3% to less than 62.5% after seven days of fermentation, and further decreased to less than 1% after AD. However, Methanoculleus persistently increased from less than 1% to 22.2-97.2% after AD, with increasing TS.…”
Section: Archaeal Communitymentioning
confidence: 93%
“…S1). A total of 1371 (19), 1390 (19), 1866 (17), 1397 (21) and 1275 (17) OTUs were assigned to P0, P1, P1A, P10 and P10A, respectively. For the samples from AD under mesophilic conditions, a total of 1342 (19), 1475 (16), 1668 (19), 1847 (21) and 1588 (22) OTUs were assigned to M0, M1, M1A, M10 and M10A, respectively.…”
Section: High-throughput Sequencing Datamentioning
confidence: 99%
“…It was also demonstrated that graphene oxide (GO) could boost methane yield and production rate in AD via enhanced direct interspecies electron transfer (DIET) [16]. Meanwhile, Zhang et al [17] reported that the addition of GO to AD reduced methane production due to acute toxicity on the microbial community. As a cost-effective CM, biochar (BC) has high potential as an additive and methane production enhancer in AD.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of ARG/MGE relative abundance was obtained in most studies (p < 0.05 for 24 study conditions, p > 0.05 for 29 study conditions). It was not case for 8/28 studies, namely V060 [39], V116 [40], W013 [41], W037 [42], W041 [43], W054 [44], WN026 [45] and WN053 [46]. As for composting, Additional file 7: Table S5 summarized different study characteristics to explore heterogeneity in Fig.…”
Section: Effects On the Relative Abundance Of Arg And Mge (N = 71 Stumentioning
confidence: 99%